ANALISIS PELAKSANAAN PROGRAM PELATIHAN DAN PENGEMBANGAN KARYAWAN DALAM MENINGKATKAN KUALITAS KERJA KARYAWAN PADA PUDAM TIRTA BINA LABUHANBATU - Riska Ferdiyanti; Feby Aulia Safrin (Transpublika Publisher, 2023)
The company has previously provided training, promoted development, and kept a pool of skilled people resources. The quality of the workforce also rises when employee performance does, which is essential for achieving corporate goals. The success of the organization is significantly influenced by employee positions. The goal of the study was to determine how well personnel development and training programs had improved work conditions at PUDAM Tirta Bina Labuhanbatu. In this study, secondary data were gathered from library sources such books, journals, and informant comments in addition to primary data collected through interviews, observations, and documentation. Data reduction, presentation, and conclusion-making were all part of data analysis. While the employee training and development programs have been implemented pretty successfully, the study found that there has been insufficient communication between leaders and employees, which has prevented them from reaching their full potential. As a result, the training provided by the company does not fully provide maximum benefits for employees, and their performance still does not reach the expected standard.